Bioinspired Load‐Bearing Hydrogel Based on Engineered Sea Anemone Skin‐Derived Collagen‐Like Protein. Issue 12 (26th August 2018) - Yang, Yun Jung; Choi, Yoo Seong; Cha, Hyung Joon
Abstract : With the help of recombinant DNA technology, many protein candidates have been investigated and engineered for biomaterial applications. Particularly, several repeat sequences with unique secondary structures have been selected as minimal building blocks for biosynthesis to improve the mechanical properties of biomaterials. However, most of these structural proteins have been limited to silk, elastin, collagen, and resilin for decades. In the present work, new repeat sequence found in sea anemone are characterized and biosynthesized into a recombinant protein (named anegen) for potential use as a load‐bearing biomaterial. Because its repeat sequence unit has a unique polyproline II structure, which is prevalently found in the triple‐helix of collagen, it is assumed to be a promising structural protein candidate that can provide conformational flexibility and elasticity. Because anegen has ≈10% tyrosine residues, inspiration is taken from di‐tyrosine crosslinking in the hinge structures of insects, which can be initiated by light activation. It is found that the anegen hydrogel shows higher mechanical properties than a gelatin hydrogel and endures a compression series without deformation. Moreover, the mechanical properties of the anegen hydrogel are controllable through different crosslinking conditions in a wide range of material applications. Importantly, the anegen hydrogel exhibited suitable cell retainability and cell morphology as an implantable biomaterial. Thus, based on its mechanical properties and biocompatibility, the anegen hydrogel can be used as a potential load‐bearing and cell‐loading scaffolding biomaterial in the tissue and biomedical engineering fields. Abstract : Many structural proteins have been exploited as biomaterials for several decades. In this work, the collagen‐like structural protein found in sea anemone's tissue is engineered as a durable hydrogel. The photo‐initiated crosslinking results in durable mechanical properties of hydrogels to be applicable for load‐bearing biomaterials. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .